CLINICO-RADIOGRAPHIC STUDY OF ODONTOGENIC CYSTS AT A TERTIARY CARE CENTRE - Ali, Kamran; Munir, Faisal; Rehman, Abdur; Abbas, Iram; Ahmad, Nofil; Akhtar, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2014)
Background: Cysts of the jaws constitute an important pathology in the oral and maxillofacial region and are broadly classified as odontogenic and non-odontogenic. Objective of this study was to document the clinical and radiographic presentation of odontogenic cysts at a tertiary care centre. Methods: In this descriptive case-series, patients presenting with features of suspected cystic lesions of the jaws were investigated using radiographs and incisional biopsy. Subjects showing clinico-radiographic features of odontogenic cyst(s) with subsequent confirmation on histopathological examination were included. Results: A total of 112 subjects were investigated for suspected jaw cysts and cystic diagnosis of odontogenic cysts was confirmed in 100 patients with 53 males (53%) and 47 females (47%). The age range of patients was from 12-55 years. Radicular cyst was the most commonly diagnosed odontogenic cyst (63%) followed by dentigerous cyst (22%) and odontogenickeratocyst (14%). Anterior maxilla was the most affected site (44%) followed by posterior mandible (30%). Conclusion: Odontogenic cysts constitute an established pathology affecting the jaws with varying frequency. This study augments the data cited from Western countries and re-emphasizes the need for early diagnosis and prompt management. It also highlights the differences in the presentation of odontogenic cysts as observed in the current series. Keywords: Cyst, Jaws, Odontogenic, non-odontogenic